(untitled) (Jurnal Bina Praja, 2024)
The law mandates public services that implement its principles. Digitalization and innovation of the service processes are necessary in today’s digital era. There are still many public reports on digital services in general, and there are still many private universities in Kalimantan that have category C/Good/Unaccredited, indicating that the process of digitization and service innovation in higher education services in Kalimantan has challenges that are not easy. This research aims to reveal how the efforts of the Higher Education Service Institution (LLDIKTI) Region XI in improving the quality of higher education services in Kalimantan Island and to find out the success factors and inhibiting factors in this effort. The method in this research is qualitative, with interviews and observations as primary data, while secondary data uses documentation and literature studies. Data analysis techniques use triangulation with data collection, reduction, presentation, and verification stages. The results showed that 1) There are five service digitization innovations intended for stakeholders or service users that continue to be developed to accommodate all types of services in accordance with service standards, 2) Service process innovation is carried out by changing the process flow in service standards from 12.4 days to 7.5 days, 3) The main supporting factors are digital leadership and human resources, 4) The main inhibiting factors are commitment and digital literacy. This shows that efforts are needed that must be supported by all aspects of an organization to carry out sustainable digitalization and service innovation.